HUBUNGAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI REMAJA (KRR) DENGAN PEMELIHARAAN ORGAN REPRODUKSI PADA REMAJA KELAS XI SMAN I BADEGAN PONOROGO - Eliya Rohmah; Fitri Nur Jannah (Akbid Harapan Mulya Ponorogo, 2018)
At the high school 1 Badegan claimed not to know about adolescent reproductive health, reproductive organs how to maintain the right to complain out whitish. Based on interviews that researchers do against a class XI student at SMAN 1 Badegan of Ponorogo, amounting to 6 people on March 30, 2014, it was revealed that not understand about adolescent reproductive health, including three students claimed that once given the socialization of doctors but is given to students XIII-grade student, class X and class XI only representative to follow. The purpose of this study was to determine the relationship of knowledge about adolescent reproductive health with the maintenance of the reproductive organs of female students in class XI IPA. Type of analytical research with cross sectional approach. The study was conducted in SMA N 1 Badegan in December 2014. The population in this study were all students of class XI IPA SMAN 1 Badegan which amounts to 91, the number of samples of 74 female students with simple random sampling technique. Variable research is knowledge of adolescents on adolescent reproductive health (independent) and maintenance of the reproductive organs (dependent). Instrument research using questionnaires. To analyze the relationship between the two variables using statistical test of Rank Spearmeant with a significance level of 0.05. Based on the results, knowledge of adolescents on adolescent reproductive health majority of respondents knowledgeable enough (55.4%) and maintenance of the reproductive organs largely sufficient (64.9%). Based on statistical test showed Rank Spearmeant ρ = 0.015 with a significance level of 5%, so 0.015 <0.05 then the Ha received means that there is a relationship of adolescent reproductive health knowledge with the maintenance of the reproductive organs with a level of closeness of relationship is 0,282, which means a low level of the relationship. From the results of these studies are expected to be able to make planning the school to increase knowledge about adolescent reproductive health, including maintenance of the reproductive organs so that students can raise awareness to maintain appropriate reproductive health knowledge.